Synthesis of compromise sum-difference arrays through time-modulation - Rocca, P.; Manica, L.; Poli, L.; Massa, A. (IET radar, sonar & navigation, 2009)
In this study, time-modulation is exploited for the synthesis of monopulse sub-arrayed antennas. The solution of the compromise sum-difference problem is obtained by setting the set of static excitations to an optimal sum set and synthesising the 'best compromise' difference pattern through a contiguous partition method based approach. The array elements are aggregated into sub-arrays controlled by means of radio frequency switches with optimised 'on' time-durations. The switch-on instants of the pulse sequences are then computed by means of a particle swarm optimiser to reduce the interferences caused by the sideband radiations. A selected set of numerical results is reported to assess the potentialities of time-modulation in dealing with the synthesis problem at hand.